Edukasi Proses Publikasi Artikel Ilmiah pada Jurnal Internasional Bereputasi - Dewi, Christine (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2024)
Conducting research and publishing the results of the research and its analysis is one of the main criteria that must be fulfilled by lecturers in order to fulfill the responsibilities of lecturers as part of the Tridharma of Higher Education. The relevance of lecturers conducting investigations, research, and publishing scientific articles is raised substantially by the demands for publication by the higher education community. According to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform (PAN RB) Number 17 of 2013 and the Regulation of the Minister of Education and Culture Number 92 of 2014 issued by the Minister of Education and Culture, academic promotion is recognized for publication in nationally accredited scientific journals as well as international reputable journals in their respective fields. This rule provides direction so that scientific publications and functional positions of lecturers in Indonesia continue to increase. The skills to write and publish scientific articles are very important for researchers, lecturers, and students in Indonesia. However, most of them still have difficulty writing down their findings in the form of scientific publications and publishing them in well-known international journals. Therefore, this activity which is part of community service is carried out to cultivate the ability to write and publish scientific publications for the benefit of students, lecturers and researchers in Indonesia. The Zoom Meeting digital platform is used for service-related operations. Researchers, lecturers, and students from various regions in Indonesia participated in this activity. The information obtained by the participants about the field of scientific writing in well-known international journals is very much. Keywords : Publication of scientific articles, Writing of scientific articles, Training of reputable journal publications.